Flat sheet metal girder with very thin metal web : Part 2 : Sheet metal girders with spars resistant to bending - oblique uprights - stiffness - Wagner, Herbert, 1900-1982 (National Advisory Committee for Aeronautics, 1931)
Noting that the stiffness of the girder increases very rapidly as Beta increases, the result can be summed up as follows: When the cross stress preponderates in one direction and when the web plate is to be given the dimensions commensurate to its stresses, it is advisable (regardless of any ensuing structural difficulties) to set the uprights at about Beta = 120 degrees, thereby lowering the weight of the plate wall 15 percent (in contrast to Beta = 90 degrees), and raising the stiffness 55 percent. But, when the cross stresses alternate and are approximately of the same intensity in both directions, or, if the web plate thickness is determined by other structural reasons, then Beta = 90 degrees should be chosen.
"February, 1931."
NACA TM No. 605.
Translated from Zeitschrift fur Flugtechnik und Motorluftschiffahrt. Vol. 20, No. 9, May 14, No. 10, May 28, and No. 11, June 14, 1929, by the National Advisory Committee for Aeronautics.
Keywords: Sheet-metal.; Girders.; Mathematics.; Struts (Engineering); Bending.; elektronické knihy; electronic books